Pengaruh Brand Ambassador Atta Halilintar terhadap Peningkatan Produk dan Layanan Bank Syariah Indonesia - Lukman Setiawan; Amiruddin Saleh (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This study investigates the influence of employing Atta Halilintar as a brand ambassador on the improvement of products and services at Bank Syariah Indonesia (BSI) through the lens of business communication. The research employs a quantitative approach with data collected via questionnaires from 100 respondents, both BSI customers and non-customers. Respondents assessed seven key variables: awareness, image, relevance, product knowledge, purchase intention, word of mouth, and engagement. The findings reveal that the brand ambassador has a moderate impact on strengthening BSI’s products and services, with average scores falling within the “fair” range of 2.76–3.1 on a four-point Likert scale. Awareness recorded the highest score of 3.1, reflecting the effectiveness of Atta Halilintar in enhancing brand recognition among the younger generation. Conversely, purchase intention received the lowest score of 2.76, suggesting that although awareness and positive image improved, they have not yet translated into higher conversion rates or actual product usage. These results highlight that the presence of a brand ambassador primarily boosts visibility and engagement but requires complementary strategies such as product education, interactive campaigns, and community-based marketing to achieve stronger customer adoption. Thus, the study underscores the importance of integrating brand ambassador initiatives with broader business communication strategies to maximize both awareness and transactional outcomes in Islamic banking.